Prevalence and associated factors of self-medication among the college students in Tehran - Arman Latifi, Ali Ramezankhani, Zahed Rezaei, Hossein Ashtarian, Behnam Salmani, Mohammad-Reza Yousefi, Mehdi Khezeli (Journal of Applied Pharmaceutical Science, 2017)
Background: Self-Medication is medicine consumption without prescription regardless of the cause, amount, and duration of use. This study was conducted to determine the prevalence of self-medication and associated factors among a sample of students of Tehran in 2016.Methods: This is a cross sectional descriptive study was conducted with participation of 1269 students from three universities in Tehran, Iran. The samples were selected by cluster sampling method. Data collection tool in this study was a researcher made questionnaire including 62 questions. Validity of questionnaire was approved by CVI and CVR approaches. Data were analyzed with SPSS version 19 and using the central indices, t-test, chi-square, Pearson correlation coefficient and logistic regression.Results: mean age of students was 21.13±1.19 years. 80.7% of participants had a history of self-medication in the past six months. The highest rate of self-medication in both genders was belonged to headache 65.4%, colds 41.9%, cough and sore throat 27.2%,. Results showed that there was a statistically significant differences between self-medication with gender, university, and level of knowledge (p
Keywords: Drug, Medicine, Self Medication.